Hepatitis B virus infection among the tribal and particularly vulnerable tribal population from an eastern state of India: Findings from the serosurvey in seven tribal dominated districts, 2021–2022 - Bhattacharya, Haimanti; Parai, Debaprasad; Sahoo, Subrat Kumar; Swain, Aparjita; Pattnaik, Matrujyoti; Mohapatra, Ira; Choudhary, Hariram; Dash, Girish Chandra; Akhtar, Nausaba; Kshatri, Jaya Singh; Bhattacharya, Debdutta; Pati, Sanghamitra (Frontiers in Microbiology, 2023)
The Global Health Sector Strategy on viral hepatitis (2016– 2021) endorsed by the World Health Assembly in 2016, called for the elimination of viral hepatitis as a public health threat by 2030. Odisha, an eastern state of India, has the 3rd highest percentage of tribal population in the country and limited information is available regarding the prevalence of HBsAg among them.The present study was undertaken to estimate the seroprevalence of hepatitis B surface antigen as well as HBV DNA almost after twelve years of the first prevalence study of HBsAg among the tribal community of Odisha.The present study attempted to understand the prevalence of HBsAg among the 35 Scheduled tribal communities and 5 Particularly Vulnerable Tribal Group (PVTG) using the 2737 number of sera collected as part of a statewide COVID-19 serosurvey,among the tribal populations of Odisha (residing in 7 districts) aged 6– 75 years. HBsAg positivity ranged between 1.79% to 2.94% across various age groups. 42.9% of HBsAg-positive individuals showed the presence of HBV DNA and the high viral load,indicating a high potential to transmit the virus.The HBsAg positivity was 14.18% and 6.06% among the PVTGs,Kutia Khond and Paudi Bhuyan,who were first time surveyed for HBsAg prevalence.The present study 1st time documents the prevalence of HBsAg among the major tribal population residing in the eastern state of the country.The study highlights the need for a statewide survey of Hepatitis B infection and risk factors,coverage and impact of the Hepatitis B vaccination programme introduced in 2010-11 in Odisha state.